2003
DOI: 10.4269/ajtmh.2003.68.286
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Wuchereria Bancrofti Microfilaria Counts in Human Blood and Parasite Uptake and Maturation in Culex Pipiens, With Observations on the Effects of Diethylcarbamazine Treatment on These Parameters

Abstract: This study examined relationships between blood microfilaria (MF) counts and parasite uptake and maturation in Culex pipiens fed on Egyptian volunteers with bancroftian filariasis. Uptake of MF and production of infective larvae (L3) were more closely correlated with MF counts in finger prick blood than in venous blood. Only a minority of ingested MF developed into L3. Few MF were ingested, and very few L3 were produced by mosquitoes that fed on infected subjects who were amicrofilaremic by 50 L thick blood sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
2
9
1
Order By: Relevance
“…As a consequence, the efficacy of a vaccine against filarial infections is likely to depend on how well it disrupts parasite immune evasion mechanisms. Given that the maintenance and transmission of filarial infections requires very few adult parasites [11] and that our previous work suggests that they are able to increase their fecundity in response to host immune attack [12], any intervention strategy should be assessed by its ability to suppress the transmissible stages, the microfilariae. Not only is this critical to reducing disease transmission, but in onchocerciasis microfilariae are the main cause of pathology.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the efficacy of a vaccine against filarial infections is likely to depend on how well it disrupts parasite immune evasion mechanisms. Given that the maintenance and transmission of filarial infections requires very few adult parasites [11] and that our previous work suggests that they are able to increase their fecundity in response to host immune attack [12], any intervention strategy should be assessed by its ability to suppress the transmissible stages, the microfilariae. Not only is this critical to reducing disease transmission, but in onchocerciasis microfilariae are the main cause of pathology.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Other studies have shown that mosquitoes fed on subjects with persistent, low-level microfilaremia following therapy ingest MF and produce infective filarial larvae. 10 The issue of treatment coverage must also be considered. No MDA program achieves complete coverage, and 80% coverage of eligible subjects (nonpregnant, more than two years of age, with no serious acute or chronic illness) is sometimes quoted as a goal for MDA programs; 11 actual coverage rates are often much lower than this.…”
Section: Introductionmentioning
confidence: 99%
“…pipiens mature to the infective stage (L3). 11 We found that while Cx. pipiens sometimes ingest MF when they feed on infected subjects with negative 50 L thick blood smears, such feedings produce very few L3.…”
Section: Introductionmentioning
confidence: 72%
“…pipiens. 11 The present project studied people with higher MF counts who were treated with two different DEC/ALB treatment regimens; subjects were restudied on multiple occasions over 12 months following treatment. A number of groups have reported effects of DEC/ALB on microfilaremia and adult worms in bancroftian filariasis.…”
Section: Discussionmentioning
confidence: 99%